The role of nutrients and probiotics in treatment of depression - N. G. Neznanov; G. V. Rukavishnikov; E. D. Kasyanov; M. A. Ganzenko; L. V. Leonova; T. V. Zhilyaeva; G. E. Mazo (Бюллетень сибирской медицины)
Currently, a growing amount of data is emerging on the role of various environmental factors (nutrients, gut microbiota, etc.) on formation of depression. The impact on these factors can be effective not only in treatment of major depressive disorder, but also in its early prevention. Therefore, a more detailed study of environmental factors in depression can lead both to a better understanding of the etiology and pathogenesis of the disorder and to optimization of approaches to its treatment. The aim of the review was to assess the potential role of a number of environmental factors associated with nutritional aspects and characteristics of individual microflora, as well as to review the prospects of a strategy for affecting these factors in treatment and prevention of depression.